Comparison between Predicted Rock Mass Classes and Actual Rock Mass Classes in Headrace Tunnel of Upper Mai Hydroelectric Project, Nepal - Chaulagai, Kanchan (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
This study involves comparison of predicted rock mass classes in design stage with actual rock mass classes of headrace tunnel of Upper Mai Hydroelectric Project. The total length of headrace tunnel is 2070.52 m. The lithology of the study area consists of gneiss, schistose gneiss and mica schist. The rock mass classifications, Q-system were used to predict rock mass classes during the design phase as well as for classify rock mass during excavation of headrace tunnel. The applicability and validity of proposed classification has been checked by comparing the prediction with actual observation after completion of excavation. It was found that the predicted classes does not exactly matches with the actual rock masses as a results effecting in construction time as well as in cost and economy of the project. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue No: 22Page: 41-44Uploaded date: January 14, 2018